On Oriental Cults from the South of the Province of Dalmatia (A few examples from East Herzegovina) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper presents the data on oriental cults from the south of the province of Dalmatia (east Herzegovina). The main research material, which was used as the source of data on the religion of the residents from the south of the province of Dalmatia, was the collection of sacrificial votive inscriptions and paintings of icons with their representations on monuments. These records are historically highly valuable because they closely portray the religion of the residents in the area of east Herzegovina in the ancient time. Given the fact that the province of Dalmatia was geographically located between the East and the West, it was the area on which numerous cults and spiritual events were found. That is why the epigraph statues are the main sources for the research of the presence of various cults, including the oriental ones, which were mostly concentrated in urban centres. This also gave us an insight into the social structure and the origin of their founders. Even though the oriental cults were present sporadically in the area of east Herzegovina (Mostar, Konjic), they were significant in terms of their content and representations. They were preserved in traces in a few votive inscriptions. Of all the oriental cults from the area of east Herzegovina, the most prominent one was the cult of Mithra, an Iranian god of light. It is believed, based on the epigraph records, that the cult of Mithra was respected by the members of various social, political, cultural, and economic circles including clerks, soldiers, merchants, the freed, and slaves. The researchers think that the cult came to the Balkans from different directions. Besides Aquilei, the cult of Mithra spread to the Danube and across Lower Pannonia. The inscription for the cult of Mithra was Sol or Sol Invictus. The epigraph statues from urban centres from the south of Dalmatia (Mostar, Konjic) testify about eastern cults which were present at the time. It can be said that the oriental cults became integral parts of the Roman culture for the residents in the south of Dalmatia.
Keywords: oriental cults (cult of Mithra); epigraph statues; the province of Dalmatia; East Herzegovina; Mostar; Konjic